We, Too, Must Love - Aldrich, Ann, 1927 May 27- (Book collections on Project MUSE., 2006)
Three years after We Walk Alone, Ann Aldrich expands on her journalistic portraits of lesbian subcultures in and around New York to include: class questions; the diverse jobs lesbians held; social cliques; differences among the "Village," "Uptown," and Brooklyn communities; and hints at the growing consciousness that would fuel later lesbian and gay rights movements. The sequel closes with sample letters from the six hundred written to Aldrich after We Walk Alone was published.